Perspektif Perawat Terhadap Penilaian Portofolio Dalam Jabatan Fungsional Perawat Di Rumah Sakit USU Medan - Cut Maria Veriana; Arpina Fajarnita (Institut Nalanda, 2023)
Background: Portfolio assessment is one method of testing job competency functional health. This assessment can provide deep strategy improve knowledge and skills in certain competencies by create planned development. Objective: This research aims to understand the implementation of portfolio assessments in the functional position of nurses at universitas sumatera utara hospital Medan. The type of research used is qualitative study with a phenomenological approach. Method: There were 14 participants in this research selected using purposive sampling technique. The instrument used was a Focus Group Discussion (FGD) guide. Data was analyzed qualitatively using content analysis. Findings: The research results identified 5 (five) themes, namely: 1) implementation of portfolio assessment, 2) obstacles in carrying out portfolio assessments in functional positions, 3) facilities supporting portfolio assessment, 4) benefits of carrying out portfolio assessment in the functional position of the nurse, and 5) expectations from the portfolio assessment. Implication: This research can be recommended to parties hospital managers to be able to carry out internal portfolio assessments The functional position of the nurse is in accordance with the in-service portfolio assessment draft functional nurse.